1996
DOI: 10.1074/jbc.271.40.24401
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between a Minimal Protein Serine/Threonine Phosphatase and Its Phosphopeptide Substrate Sequence

Abstract: The protein phosphatase encoded by coliphage lambda (PP) was found to be the equivalent of the minimal catalytic core of serine/threonine protein phosphatases (PP) by biochemical and mutational criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…This probably underscores the more primitive evolutionary status of this obligatory parasite compared with its eukaryotic hosts. On a similar note, PP , a prokaryotic protein phosphatase, was recently been shown to contain very little sequence information beyond the conserved domains and, thus, appeared to be equivalent to the minimal catalytic core of the larger eukaryotic phosphatases (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This probably underscores the more primitive evolutionary status of this obligatory parasite compared with its eukaryotic hosts. On a similar note, PP , a prokaryotic protein phosphatase, was recently been shown to contain very little sequence information beyond the conserved domains and, thus, appeared to be equivalent to the minimal catalytic core of the larger eukaryotic phosphatases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Section 1734 solely to indicate this fact. A preliminary account of this work was presented at the Molecular Parasitology Meeting VII in Woods Hole, MA (September [15][16][17][18][19]1996).…”
Section: Methodsmentioning
confidence: 99%
“…The PP1␣ catalytic core (residues 41-269) was expressed in bacteria and purified as described previously (15). Recombinant human inhibitor-1 was expressed, purified, and phosphorylated as described by Connor et al (16).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies (30,31) suggested that extensive deletions of C-terminal sequences impaired or destabilized PP1␣ activity. Although recombinant PP1␣-(1-297) demonstrated phosphorylase phosphatase activity equivalent to that of full-length PP1␣, PP1␣-(1-276) was not expressed in bacteria.…”
Section: Purification Of Recombinant Pp1 Catalytic Subunits-mentioning
confidence: 99%